Estrogen Receptor beta, through Sp1, recruits a corepressor complex to the Estrogen Receptor alpha gene promoter in breast cancer cells - Zito, Domenico; Sisci, Diego; Andò, Sebastiano (My University, 2012)
Human Estrogen receptors alpha (α) and beta (β) are essential components of a complex signal transduction pathway that regulates mammary growth and development. Several studies have reported that normal breast tissues display a relative higher expression of ERβ than ERα, which drastically changes during breast tumorogenesis. Thus, it is reasonable to suggest that a dysregulation of the two estrogen receptor subtypes may induce breast cancer development. However, the molecular mechanisms involved in the potential opposing roles played by the two estrogen receptors on tumor cell growth still needs to be elucidated. In the present study, we have demonstrated that ERβ overexpression in breast cancer cells decreases cell proliferation and down-regulates ERα mRNA and protein content, with a concomitant repression of estrogen-regulated genes. Transient transfection experiments, using a vector containing the human ERα promoter region, showed that elevated levels of ERβ down-regulated basal ERα promoter activity. Furthermore, site-directed mutagenesis and deletion analysis revealed that the proximal GC-rich motifs at −223 and -214 are critical for the ERβ-induced ERα down-regulation in breast cancer cells. This occurred through ERβ-Sp1 proteinprotein interactions within the ERα promoter region and the recruitment of a corepressor complex containing the nuclear receptor corepressor NCoR, accompanied by hypoacetylation of histone H4 and displacement of RNA polymerase II. Silencing of NCoR gene expression by RNA interference reversed the down-regulatory effects of ERβ on ER α gene expression and cell proliferation Collectively, these results suggest a novel mechanism by which overexpression of ERβ, through NCoR, is able to down regulate ERα expression, thus repressing ERα’s main role on breast cancer cell growth
Dottorato di Ricerca in Biochimica Cellulare ed attività dei Farmaci in Oncologia, XXV Ciclo, a.a. 2011-2012
Keywords: Biochimica; Recettori; Estrogeni